Impact of human T‐cell leukemia virus type 1 on living donor liver transplantation: a multi‐center study in Japan. (15th May 2016) - Yoshizumi, Tomoharu; Takada, Yasutsugu; Shirabe, Ken; Kaido, Toshimi; Hidaka, Masaaki; Honda, Masaki; Ito, Takashi; Shinoda, Masahiro; Ohdan, Hideki; Kawagishi, Naoki; Sugawara, Yasuhiko; Ogura, Yasuhiro; et al.
Abstract: Background: The natural history of human T‐cell leukemia virus type 1 (HTLV‐1), which causes adult T‐cell leukemia (ATL) or HTLV‐1 associated myelopathy, after liver transplantation is unclear. Methods: We conducted a nationwide survey to investigate the impact of HTLV‐1 status on living donor liver transplantation (LDLT) in Japan. We analyzed the cases of 82 HTLV‐1‐positive recipients and six HTLV‐1‐negative‐before‐LDLT recipients who received a hepatic graft from HTLV‐1‐positive donors. Results: Adult T‐cell leukemia developed in five recipients who ultimately died. Of these five, two received grafts from HTLV‐1‐positive donors and three from HTLV‐1‐negative donors. The 1‐, 3‐, and 5‐year ATL development rates were 4.5%, 6.5%, and 9.2%, respectively. Fulminant hepatic failure as a pre‐transplant diagnosis was identified as an independent risk factor for ATL development ( P = 0.001). The 1‐, 3‐, and 5‐year survival rates for HTLV‐1‐positive recipients who received grafts from HTLV‐1‐negative donors were 79.9%, 66.1%, and 66.1%, and from HTLV‐1‐positive donors were 83.3%, 83.3%, and 60.8%, respectively. The 1‐year survival rate for HTLV‐1‐negative recipients who received grafts from HTLV‐1‐positive donors was 33.3%. Conclusions: Fulminant hepatic failure is an independent risk factor for ATL development in HTLV‐1‐positive recipients. Grafts from HTLV‐1‐positive living donors can be transplanted into selected patients. Abstract : Highlight In this nationwide study investigating the impact of HTLV‐1 status on living donor liver transplantation in Japan, Yoshizumi and colleagues revealed that the outcomes of HTLV‐1‐positive recipients who underwent living donor transplantation were acceptable. Fulminant hepatitis was the only identified risk factor for adult T‐cell leukemia in HTLV‐1‐positive recipients.